Cervical exenteration and its variants for locally advanced thyroid cancer: when, why, and how?. Issue 2 (28th April 2023) - Piazza, Cesare; Lancini, Davide; Paderno, Alberto
Abstract : Purpose of review: To describe the modern surgical approach for management of advanced thyroid cancers infiltrating the cervicovisceral axis with special attention to well differentiated tumors not amenable to organ-sparing techniques. In particular, cervical exenteration, herein defined as the sum of total thyroidectomy, central compartment and lateral neck dissections, variously associated with total laryngectomy and possible partial or total pharyngoesophagectomy, represents an extreme surgical procedure that, in properly selected cases, allows for reasonable palliation of central compartment life-threatening signs/symptoms if not cure for an advanced oncologic condition. Recent findings: Cervical exenteration is not contraindicated by the presence of limited distant metastases at presentation. Even though it requires that the patient is in general good health as it can be associated with a number of complications and long in-hospital stay, when appropriately planned and performed according to the most recent reconstructive nuances, it allows good oncologic outcomes that are not inferior to those described for similarly advanced primaries of the upper aerodigestive tract. In addition, quality of life and functional results are not significantly different from those described after total laryngectomy for primary laryngeal squamous cell carcinomas. Summary: Cervical exenteration requires a tertiary, expert, multidisciplinary effort in terms of diagnosis, surgical performance, and postoperative care. A patient-centered decision process is strongly warranted taking into consideration alternative therapeutic and symptom-based palliative strategies.